Comparative Analysis of the Effects of Two Different Drill Designs on Insertion Torque and Primary Stability during Osteotomy – An In Vivo Animal Study - Sudhakar Arpudaswamy; S. Syed Asaraf Ali; Suma Karthigeyan; A Ponnanna; Yamini Nadhini; R Eazhil (Journal of Pharmacy and Bioallied Sciences)
Objective: This study aims to evaluate the effects of two drill designs on insertion torque (IT) and implant stability quotient (ISQ) during osteotomy. Methodology: This in vivo animal study involved eight female New Zealand white rabbits divided into two groups: Group A underwent osteotomy using standard drills from the Zimmer surgical kit, and Group B used Densah drills. IT values and ISQ were taken during and after implant placement. Rabbits received premedication, and postoperative care was provided. Results: Significant differences in peak IT were observed between the two groups, with Group B demonstrating a statistically significant advantage. However, no significant differences were found in ISQ between the groups. Conclusion: This study highlights the potential benefits of osseodensification in enhancing primary stability during osteotomy.